Emotional Abuses of Slum Women by their Husbands in Kathmandu Valley - Paudel, Manusha (Journal of Population and Development, 2020)
Emotional abuse is a hardest form of abuse to recognize and globally it is a major public health problem. This study aims to explore the associated factors among slum married women in Kathmandu valley. It has used primary data from slum areas of Kathmandu valley and this study confined with married women only. Result showed more than two fifth (42%) women’s husband get angry if their wives talked with another male members either they are relatives or friends. The percent of emotional abuse was high where respondents did not attend school (33%) than who attended school (21%). Uniquely, study found that all alcohol user husbands insulted their wife in front of others and threatened or made worried. Despite that whose husbands did not use alcohol, their wives were not fallen on any types of emotional abuse. Additionally, quarrelling habit of husbands is also leading factor of emotional abuse. Findings of this study demonstrated that several factors are associated with emotional abuse including alcohol use, education, and occupation and battering habit. On the other hand, non-use of alcohol, high level of education, skilled occupation, and non-battering habit could protect women against emotional abuse by their husband. Therefore, interventions should focus on these issues for both men and women.